Critical Examination of Müller Glia-Derived in vivo Neurogenesis in the Mouse Retina - Xie, Ye; Chen, Bo (Frontiers in Cell and Developmental Biology, 2022)
Müller glia (MG) are a potential source of stem cells in the mammalian retina that could replenish lost retinal neurons for vision restoration. Unlike their counterpart in zebrafish, mammalian MG are quiescent and they do not spontaneously generate new retinal neurons. In recent years, extensive research efforts have been made to unlock the regenerative capabilities of Müller glia (MG) for de novo regeneration of retinal neurons in mice. Here, we discuss current research progress on MG-derived in vivo neurogenesis in the mouse retina, focusing on the use of stringent fate mapping techniques to evaluate and validate de novo regeneration of retinal neurons through the reprogramming of endogenous MG. Establishing stringent experimental criteria is critical for examining current and future studies on MG-derived regeneration of photoreceptors, retinal inter-neurons, and retinal ganglion cells.